THE REFLECTIONS OF MATERNAL PASSIONS AS ASSERTED IN Y. B. MANGUNWIJAYA’S MBAH BENGUK - Yuliastuti, Anicleta; Pujimahanani, Cahyaningsih; Pasopati, Rommel Utungga (Seshiski: Southeast Journal of Language and Literary Studies, 2021)
Today, the discourse of feminism pays more attention to correlations between women, motherhood, and society rather than trying to make women equal to men. Julia Kristeva explains maternal passion as motherhood’s characteristic that relates to the biological state of the sacred womb and the sociological aspect of having children. Mbah Benguk in Y. B. Mangunwijaya’s work tells about a grandmother who takes care of her two disabled grandchildren left by their mother. Mangunwijaya does not attack feminism, yet he underlines the crucial role of the mother. The question is; how is maternal passion reflected in Y. B. Mangunwijaya’s Mbah Benguk? Using the qualitative method, cultural concepts are used to explain the relations between Mangunwijaya’s story and Kristeva’s perspectives. Tensions between biological concepts of woman and sociological ideas of the mother are contradicted. Being a mother shows more passion than emotion as seen in children’s language as a reflection of their mother. Motherhood is the sublimation of a woman’s desire for her children. In conclusion, the story of Mangunwijaya is enriched through Kristeva’s perspective, especially in how a woman should be present as the maternal passion of the womb and the caregiver to her children.